Characterizing potential subtypes and influencing factors of burnout in emergency department nurses by latent profile analysis - Lan, Lin; Chen, Xiaoli; Zhang, Hao; Zhong, LuYing; Ye, Lei (Frontiers in Public Health, 2025)
Objective:This study aims to explore the heterogeneity of burnout among emergency department nurses, identify the factors influencing burnout in different subtypes of emergency nurses, and provide targeted strategies and measures to reduce burnout in emergency department nurses.MethodsA cross-sectional survey was conducted from December 26, 2023, to January 18, 2024, involving 1,555 emergency nurses from 30 tertiary hospitals in China. The survey was distributed via an online questionnaire platform, which included general demographic information and the Maslach Burnout Inventory (MBI). The collected data were analyzed using latent profile analysis, Kruskal–Wallis H test, and multiple logistic regression.ResultsA total of 1,555 questionnaires were sent out in this survey, and finally 1,540 were included for data analysis. The average burnout score among emergency nurses was (4.77 ± 6.16). Occupational burnout could be categorized into three subtypes: low burnout-low professional efficacy (C1), low burnout-high professional efficacy (C2), and high burnout-low professional efficacy (C3). The proportions of these subtypes were 41%, 32.3%, and 26.7%, respectively. Significant differences in the latent categories of burnout were observed for age (χ2 = 31.749, P < 0.001), education level (χ2 = 6.778, P = 0.034), professional title (χ2 = 21.928, P < 0.001), years of work (χ2 = 29.269, P < 0.001), weekly working hours (χ2 = 52.493, P < 0.001), number of night shifts (χ2 = 34.685, P < 0.001), and monthly income (χ2 = 18.994, P < 0.001).ConclusionOccupational burnout is prevalent among emergency nurses, with significant heterogeneity in burnout types. Burnout is associated with age, education level, professional title, number of night shifts, weekly working hours, and monthly income. The heterogeneity of burnout subtypes and their influencing factors provides a basis for future personalized interventions.